Running a Successful Textile Diploma Course in a Remote Indian Town-A Case Study - Raichurkar, Pramod; Dorugade, Vishnu; Waychal, Pradeep (Journal of Engineering Education Transformations, 2015)
Indian Textile industry is unique in many ways. It is the second largest employer and depends heavily on the largest employer - agriculture. It has been successful in automating most of its operations. So, instead of employing unskilled labor, it is now looking for skilled labor and facing significant challenges in finding them - even though the national unemployment has been hovering at around 9 %. The situation demanded a different approach such as setting up textile training courses in a remote area where employment is a larger issue and working closely with the industry to develop highly employable graduates. The paper describes a successful case study ofsetting up a four year diploma course in close collaboration with the industry in a remote town of Shirpur in North Maharashtra (India). That required a team of faculty that could inspire confidence in the industry personnel and adopting progressive educational methods such as active learning and mentoring. The school was started in 2007 and has produced 200 diploma holders with cent percent placement. This is far above similar other institutes. These students from rural and semi-rural area are fetching salaries that are higher than even graduate engineers. Thus the experiment has succeeded in its twin objectives of rural development and workforce development for one of the most critical industry of the country.